A 10 years update of effects of exercise on depression disorders—in otherwise healthy adults: A systematic review of meta-analyses and neurobiological mechanisms - Henning Budde; Nina Dolz; Anett Mueller-Alcazar; Fabian Schacht; Bruna Velasques; Pedro Ribeiro; Sergio Machado; Mirko Wegner (PLoS ONE, 2025)
Background Depression is one of the most common mental illnesses worldwide and is a major burden for those affected. As conventional therapies do not always work and are also associated with side effects, alternative treatment methods are urgently indicated. In the past, exercise has established itself as a seemingly good alternative treatment method. The aim of this work is to provide a state of the art review and to check whether there are new findings since the publication of the article by Wegner and colleagues 10 years ago. Methods A systematic literature search was conducted. This included searching for appropriate literature in databases such as PsycINFO, PsychARTICLES, PubMed, CINAHL Complete, SocINDEX, SPORTDiscus and Psyndex. Effect sizes calculation and evaluation of the methodological characteristics (AMSTAR 2) were carried out. Finally, the neurobiological explanations for the effect of exercise on depression are discussed. Results Eleven meta-analyses met the inclusion criteria, with the total sample consisting of 16.255 participants and 229 individual studies. The most frequently implemented intervention was aerobic exercise, while the intervention in the control groups was usually no treatment, waiting list, or attention/activity placebo. The pooled results indicate a moderate clinical effect, suggesting the positive effect of exercise and physical activity in reducing depressive symptoms (SMD = -0.61, 95% CI [− 0.78; -0.43], p = <0.01). Conlcusion The medium but consistently positive effects that were found in the present study place exercise/ physical activity as a promising and helpful alternative for adults with depression. The positive effect of exercise and physical activity could potentially be explained by neurological changes. However, the exact mechanisms underlying the antidepressant effects are still unclear.